An Unified Framework for Measuring E-Service Quality - Alanezi, M. A.; Sellami, A. (Engineering, Technology & Applied Science Research, 2019)
Companies continually seek efficiency by utilizing the rapid advances in technology to improve their electronic services (e-services). A perusal of the literature shows varying approaches for measuring e-service quality; these approaches have found little consent among reviewers. Therefore, this study attempts to provide a new framework, a roadmap, as a useful model for researchers to measure user perception of e-service quality. For this model, an extensive study is carried and these study findings indicate that system functionality, procedure, content, user support, and manageability should be included in an empirical research model for measuring e-service quality.